2002
DOI: 10.1080/0703633022000038959
|View full text |Cite
|
Sign up to set email alerts
|

EU Structural Funds, Regional Capabilities and Enlargement: Towards Multi-Level Governance?

Abstract: Given GDP variations across CEE regions and with CEE regional structures and development processes only emerging recently, the cohesion situation under EU enlargement is considerably more challenging than when current EU regional policy was launched in 1988. Yet even that reform ran into problems given heterogeneity in the forms of regional governance across the EU. This needs to be fully recognised in the context of enlargement where pre-accession funding has focused on the national level, leading in some cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 16 publications
0
24
0
3
Order By: Relevance
“…Due to the centralized national traditions of the CEEC, sub-national entities in these states were nonexistent or lacked competencies and political power, and the European Commission's incentives to provide policy guidance for territorial reorganization in order to meet the partnership requirements of receiving Structural Funds assistance were greater than in the cases of its incumbent member states or previous enlargements (Bailey & De Propris 2002a;Baun 2002;Brusis 2002;Getimis 2003;O'Dwyer 2006;Pitschel & Bauer 2009;Sturm & Dieringer 2005). Therefore, Europeanization 'Eastern-style' stresses the hierarchical and impositional aspects of domestic adaptation, fostered by 'conditionality' (Goetz 2005;Grabbe 2001).…”
Section: The Context Of Ceecmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the centralized national traditions of the CEEC, sub-national entities in these states were nonexistent or lacked competencies and political power, and the European Commission's incentives to provide policy guidance for territorial reorganization in order to meet the partnership requirements of receiving Structural Funds assistance were greater than in the cases of its incumbent member states or previous enlargements (Bailey & De Propris 2002a;Baun 2002;Brusis 2002;Getimis 2003;O'Dwyer 2006;Pitschel & Bauer 2009;Sturm & Dieringer 2005). Therefore, Europeanization 'Eastern-style' stresses the hierarchical and impositional aspects of domestic adaptation, fostered by 'conditionality' (Goetz 2005;Grabbe 2001).…”
Section: The Context Of Ceecmentioning
confidence: 99%
“…In the regional policy domain, the lack of institutional detail tied to conditionality, due to the fact there is no basis for such an EU intervention in the Treaties (Brusis 2002, p. 31), constrained the impact of the EU (Bailey & De Propris 2006;Sturm & Dieringer 2005). Indeed, the influence of domestic historical institutional traditions affected development of the sub-national level in CEEC and introduced variances in how these states responded to EU influence (Bailey & De Propris 2002aHughes et al 2004;Getimis 2003).…”
Section: The Context Of Ceecmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies suggest that while the Commission initially sought to advance regionalization in CEE countries, inspired by ideals of multi-level governance, as accession grew closer its position shifted to ensuring that the funds were absorbed on time, even if this meant (2002)(2003)(2004)(2005)(2006) they were managed centrally through national ministries (Marcou 2002, 25;Leonardi 2005, 164). Bailey and De Propris's (2002) study of the Czech Republic, Estonia, Hungary, Poland and Slovenia identified national government 'gatekeepers' 'firmly in control' of subnational actors, who were able to participate in but not significantly influence the policy process. Gordon's (2004, 2005) research on Estonia, Hungary, Poland and Slovenia emphasized the importance of historical institutional traditions in each state in shaping the degree of regionalization emerging, echoing the findings of the earlier research on the EU15.…”
Section: Existing Studiesmentioning
confidence: 99%
“…Since the introduction of the so-called Delors I Package making eff ective the provisions of the Single European Act (SEA) of 1986, the European Union's structural funds have become chief instruments intended to ensure economic and social cohesion at the Community level (Bailey and De Propris, 2002; De Michelis and Monfort, 2008; Paraskevopoulos and Leonardi, 2004). With the transformation of the principles of the Community's regional policy, there was a growing conviction of a great importance of those two cohesion dimensions for its development.…”
Section: Introductionmentioning
confidence: 99%